CORRELATION OF VOLUME BLOOD CIRCULATION IN THE HEPATIC ARTERY AND THE STATE OF MICROCIRCULATORY BLOODSTREAM OF THE TRANSPLANTED LIVER AFTER ITS REVASCULIZATION - D. A. Granov; I. I. Tileubergenov; S. V. Shapoval; D. N. Maystrenko; K. M. Pozharissky; A. G. Kudaybergenova; V. V. Borovik; I. O. Rutkin (Вестник трансплантологии и искусственных органов, 2014)
Aim: optimization of the surgical treatment policy with orthotopic liver transplantation (OLT) depending on the results of intraoperative fl owmetry and the state of intrahepatic microcirculatory bloodstream according to immunohistochemical (IHC) study of microspecimens of the donor’s liver.Materials and methods. 60 patients are included in the study. Group I (n = 30) comprised of patients for whom it was not necessary to perform any additional interventions on the bloodstream in the hepatopancreatobiliary area during OLT. Group II (n = 30) had patients with insuffi cient arterial blood supply for the graft in the intraoperative stage where it was needed to perform additional and/or repeated interventions in the arteries of the hepatopancreatobilliary area. Intraoperative fl owmetry with assessment of the volume blood circulation (VBC) in the hepatic artery (HA) was carried out in the both studied groups. Reference value of VBC was 100 ml/min and higher. Before and after reperfusion in the liver biopsy material we performed immunohistochemical study with the use of endothelial marker CD 31 with subsequent morphometric estimation of the specifi c square of the microvascular bloodstream.Results. In both groups there was no change in the specifi c square in the areas of portal tract and central vein before and after restoring blood fl ow. In the second group, an 8 times increase of the specifi c square of sinusoids was observed after restoring blood fl ow (р < 0,01).Conclusion. Intraoperative fl owmetric control of the blood fl ow allows in due time to perform surgical correction of the graft arterial blood supply during OLT, and it reduces the risk of thrombosis up to 0%. The value of VBC in the hepatic artery (HA) has reliable dependence upon the state of microcirculatory bloodstream of cadaveric donor’s liver after reperfusion.